Emulgel Formulation of Purified Extract of Moringa (Moringa oleifera L.) Leaf - Wuryandari, Tutik; Sugihartini, Nining; Kintoko, Kintoko (Folia Medica Indonesiana, 2019)
Moringa oleifera, known as moringa, is reported to have a high source of natural antioxidants, especially vitamin E. The formulation of purified Moringa leaf extract is needed so that the vitamin E content in it is more maximal. This study aimed to determine the levels of vitamin E in extracts after purification, physical property test of emulgel with variations in extract concentration and vitamin E levels in emulsions. The study was started from the extraction using maceration method with petroleum ether solvent, followed by extract purification using column chromatography with n-hexane solvent. The results of the purified extract were then formulated into emulgel with three concentrations of 3% (F1), 6% (F2) and 9% (F3). Emulgel was then evaluated for physical characteristics (pH, viscosity, adhesion, dispersion and stability). Determination of vitamin E levels was carried out on purified extract samples and on each formula. The results of non-specific standardization of extracts included ash content, acidic insoluble ash content were higher than those of Indonesian Herbal Pharmacopoeia literature and drying losses were lower compared to literature. Specific standardization of extracts was the content of vitamin E in 1.40% PE extract and 8.02% purified extract. In the test of emulgel physical characteristics, an increase in the concentration of the extract caused an increase in viscosity and decreased emulgel dispersion power. Whereas, tthe pH and sticky power remained the same. Storage hds an effect on decreasing the physical characteristics of emulsions especially on adhesion. Increased extracts also caused an increase in the levels of vitamin E in the purified extract of moringa leaf emulgel.